Desenvolvimento de novas formulações de vacinas inativadas e de subunidades utilizando o parvovírus suíno como modelo - Amanda Soriano Araujo (2012)
The objective of this work is to develop new formulations of inactivated and subunit vaccines using porcine parvovirus (PVS) as a model. Four adjuvant formulations have been developed, i) multiple emulsion, ii) microemulsion, iii) chitosan microspheres and iv) implants of chitosan. It have been developed a virus like particle (VLP-PVS) vaccine using baculovirus system. 1024 UHA of PVS suspension was used to produce the vaccines. The matches produced were tested for stability, safety, sterility and potency. The immune response was evaluated using vaccination of guinea pigs and the monitoring of antibody titers by hemagglutination inhibition test. The safety test showed that only the multiple emulsion was not approved by causing extensive skin land muscle lesions in the guinea pigs. The PVS vaccines with chitosan microparticles or implants of chitosan or microemulsions increased the titer of antibodies. And PVS-VLP was capable of inducing the production of high titers of antibodies to swine parvovirus even without the presence of adjuvant in the vaccine composition.